PERAN SHOPPING ENJOYMENT MEMEDIASI PENGARUH HEDONIC MOTIVATION TERHADAP IMPULSE BUYING PADA FENOMENA PANDEMI COVID-19 - Udiyana, Ida Bagus Gede Prabawa Putra; Oktora Panasea, I Gede Nandya (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.08.TAHUN.2023DO - 10.24843/EEB.2023.v12.i08.p16, 2023)
The purpose of this study is to explain the role of shopping enjoyment in mediating hedonic motivation on impulse buying in the time frame of the COVID-19 pandemic. This research was conducted on customers of Trans Studio Mall Bali. The number of samples used in this study were 91 respondents, using purposive sampling method. Data was collected through a questionnaire. The analysis technique used is path analysis. Based on the results of the research conducted, it was found that hedonic motivation has a positive and significant effect on impulse buying; hedonic motivation has a positive and significant effect on shopping enjoyment; shopping enjoyment has a positive and significant effect on impulse buying; and shopping enjoyment acts as a mediating variable between hedonic motivation and impulse buying. Based on the findings of this study, it can be concluded that good hedonic motivation and shopping enjoyment greatly affect the impulse buying of customers at Trans Studio Mall Bali. Instead, the management of Trans Studio Mall Bali still pays attention to the quality of services offered and the convenience of the shopping atmosphere, especially regarding safety, health, and the implementation of health protocols in an effort to increase impulse buying